A systematic review and meta‐analysis investigating the impact of childhood adversities on the mental health of LGBT+ youth. Issue 2 (10th May 2022) - Jonas, Lucy; Salazar de Pablo, Gonzalo; Shum, Mamie; Nosarti, Chiara; Abbott, Chris; Vaquerizo‐Serrano, Julio
Abstract: Background: The presence of trauma as a backdrop to the lives of LGBT+ youth has been recognised in recent literature. LGBT+ youth report a higher frequency, severity and pervasiveness of adverse childhood experiences when compared to their heterosexual and cisgender counterparts. This exposure has been directly related to an increased risk of mental health problems. Method: A systematic literature search of Medline, Embase, PsycINFO, PubMed and Web of Science was conducted from the date of their inception until the 1st September 2021. The study protocol was registered in PROSPERO (CRD42021240472). Results: A total of 27 studies satisfied the inclusion criteria and were used in the systematic review, representing 199, 285 participants, 26, 505 of whom identified as LGBT+ (mean age 16.54). Female participants (ranging from 11% to 74%) and white participants (7.7%–96%) made up the largest percentage of most samples. Depressive symptoms were the most commonly described psychiatric outcome ( n  = 17, 63%), followed by anxiety symptoms ( n  = 6, 31.5%). 18 studies provided meta‐analysable data, compromising 21, 781 LGBT+ young people. LGBT+ youth reported a higher prevalence of adverse experiences in comparison to their heterosexual or cisgender counterparts ( p  < .001), with sexual abuse representing the most commonly reported experience (29.7%), followed by verbal abuse (28.7%), physical abuse (26.5%) and cyberbullying (19.1%). LGBT+ youth were also at a heightened risk of mental health disorders ( p  < .001), with 36.9% and 31.5% of sample meeting the clinical criteria for depression and anxiety, respectively. Conclusions: Continued advocacy is needed from communities and Allies to support and empower LGBT+ youth in the face of adversity. Longitudinal and longer‐term studies are required to further understand the relationship between adverse experiences in LGBT+ youth and the impact on mental health.